Effect of hot air drying on total phenolic content and antioxidant capacity of red Pitahaya (Hylocereus guatemalensis) peel - Castillo-Zapata, Katerin C. (2024)
Red pitahaya (Hylocereus guatemalensis) peel is a by-product of pulp and juice production, which is often underutilized due to the lack of scientific information on how to preserve it in a manner that minimally affects its bioactive compounds. The objective of this study was to evaluate the effect of hot air drying on the total phenolic content (TFC) and antioxidant capacity (AC) by DPPH radical scavenging (%) of red pitahaya peel. The peel was separated from the pulp, cut into four equal parts and subjected to hot air drying. Drying was carried out at temperatures of 40, 50, 60, 60, 70, 80 and 90 °C for a period of 1 080 min. The peel was ground (particles < 850 μm), the extract (50 mg/mL) was obtained using 80% methanol as solvent, and the TPC and AC were determined. The influence of drying temperature was significant (p<0.05) on TPC and AC as drying temperature increase of 40 to 90 °C; TPC values ranged of 116.7 ± 26.0 to 328.8 ± 57.5 mg gallic acid equivalent/100 g dry peel on dry basis and AC also increased of 22.22 ± 0.06 to 50.00 ± 0.12% DPPH radical inhibition. These results indicate that hot air drying at temperatures of 50 to 90 °C can be used to obtain dried red pitahaya peel with low free moisture and without affecting TPC and AC.